Comparative Impact of Maternal vs. Paternal Rejection on the Symptoms of Borderline Personality Disorder in a Clinical Population - Shahid, Shelina Fatema Binte (Journal of Neonatal Surgery, 2025)
Background: Borderline Personality Disorder (BPD) refers to a serious mental health problem involving mood swings, lack of self-control, and unclear self-image, which is also associated with issues in childhood relationships. Objective: This study aims to compare the impact of maternal versus paternal rejection on the severity of BPD symptoms in Bangladeshi populations. Methodology: It was a cross-sectional descriptive study. The participants were selected purposively from five psychiatric outpatient departments of Bangladeshi hospitals. Structured Clinical Interview for DSM-IV Axis II Disorders (SCID-II), a socio-demographic questionnaire, and the Parental Acceptance-Rejection Questionnaire- Mother (PARQ-M) and Parental Acceptance-Rejection Questionnaire- Father (PARQ-F) were administered on 40 BPD-diagnosed subjects (age group 18–46). Data analysis was done by SPSS v26.0 software to conduct the analysis and conduct Pearson and Kendall’s Tau-b correlation tests. Approval for the study was given by the Ethical Approval Committee of the Department of Clinical Psychology and the Ethical Approval Committee of the Biological Science at the University of Dhaka. Result: Most of the participants were found to be women, with the average age being 28.2 years. The amount of maternal rejection (67.5%) was notably higher than the amount of paternal rejection (41%). The relationship between maternal rejection and the severity of BPD was strongly and positively correlated (r = 0.304, p = 0.028), whereas the correlation between paternal rejection and BPD severity was weaker but significant (tau b = 0.210, p = 0.044). The regression model showed maternal hostility to be a significant predictor of BPD severity (beta = 0.489, p = 0.001), with 23.9 percent of the variance being explained (R 2 =0.239). Scatterplots and residual plots confirmed the statistical results, pointing to them as the main causes of BPD severity. Conclusion: Maternal hostility toward a child is much more strongly linked to the occurrence and severity of BPD symptoms compared to paternal acts of rejection. These findings highlight the value of paying attention to a mother’s role in therapy for BPD.